2022
DOI: 10.1029/2021gc010020
|View full text |Cite
|
Sign up to set email alerts
|

Strong ULVZ and Slab Interaction at the Northeastern Edge of the Pacific LLSVP Favors Plume Generation

Abstract: The northeastern margin of the Pacific Large Low Shear Velocity Province (LLSVP) is particularly interesting as many seismic modeling studies have suggested the presence of multiple structural anomalies in this lowermost mantle region. There is a strong velocity change from the interior of the Pacific LLSVP toward the margin, inferred to be a high velocity, post-perovskite lens thins toward the edge while an ultra-low velocity zone (ULVZ) layer increases in thickness (Lay et al., 2006). To et al. ( 2011) also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 63 publications
(87 reference statements)
0
30
0
Order By: Relevance
“…Our study region is to the southeast of Hawaii, at the edge of the Pacific LLVP. Figure 1c shows the raypath coverage and the locations of previously detected ULVZ structure in this region (Lai et al, 2022;Sun et al, 2019;Yu & Garnero, 2018), in addition to the low velocity features mapped by Jenkins et al (2021). Early studies using core-reflected P waves suggested a ∼10 km thick basal layer with velocity reductions of approximately 10% in our study region (e.g., Mori & Helmberger, 1995;Revenaugh & Meyer, 1997).…”
Section: Study Regionmentioning
confidence: 71%
See 2 more Smart Citations
“…Our study region is to the southeast of Hawaii, at the edge of the Pacific LLVP. Figure 1c shows the raypath coverage and the locations of previously detected ULVZ structure in this region (Lai et al, 2022;Sun et al, 2019;Yu & Garnero, 2018), in addition to the low velocity features mapped by Jenkins et al (2021). Early studies using core-reflected P waves suggested a ∼10 km thick basal layer with velocity reductions of approximately 10% in our study region (e.g., Mori & Helmberger, 1995;Revenaugh & Meyer, 1997).…”
Section: Study Regionmentioning
confidence: 71%
“…1. A prominent S* postcursor, visible directly after the S* phase and modeled as being due to an ULVZ by Lai et al (2022), is (marked with a pink box in Figure 2a). As this waveform feature has been modeled and explained before, we do not focus on it in our analysis.…”
Section: Results: Waveform Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Galápagos ULVZ falls into the category of broad-scale mega-ULVZs, which are so far uncovered by diffracted phases. Other occurrences are mapped in 3D near Hawaii (Cottaar and Romanowicz, 2012;Jenkins et al, 2021;Lai et al, 2022;, Samoa (Thorne et al, 2013), and Iceland ; these are shown in Fig. 7 combined with the global database of ULVZs by (Yu and Garnero, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…While only a fraction of the core-mantle boundary has been targeted for these anomalies, there is a weak trend that these patches appear within or near the LLVPs (Yu and Garnero, 2018). This relationship is however certainly true for the broadest of ULVZs that have been mapped in 3D (Cottaar and Romanowicz, 2012;Thorne et al, 2013;Jenkins et al, 2021;Lai et al, 2022;, and can be dubbed 'mega-ULVZs' after Thorne et al (2013).The three mega-ULVZs currently mapped lie in the vicinity of the Hawaiian, Icelandic and Samoan hotspots, and such large structures appear otherwise rare, at least across a large swath of the Pacific (Kim et al, 2020).…”
Section: Introductionmentioning
confidence: 99%